Longitudinal assessment of the temporal stability and predictive validity of the Revised Paranormal Belief Scale - Dagnall, Neil; Denovan, Andrew; Drinkwater, Kenneth Graham (Frontiers in Psychology, 2023)
The Revised Paranormal Belief Scale (RPBS) is the prevailing measure of supernatural credence. However, there exists only limited evidence to support the temporal stability and predictive validity of the instrument over time. Acknowledging this, the present study assessed the test-retest reliability of the RPBS using a large, heterogeneous sample across multiple trials. In addition, predictive validity was tested using a longitudinal statistical model, which focused on allied health outcomes (Perceived Stress and Somatic Complaints). A sample of 1665 (Mage = 54.40, 853 females, 804 males, five non-binary, and three not disclosing of gender) completed study measures at three time points separated by two month intervals. Prior to assessing temporal stability, assessment of structural validity and longitudinal invariance occurred. Test-retest reliability of the RPBS was in the moderate to high range across time intervals, and good internal consistency was observed. Furthermore, satisfactory stability coefficients existed for RPBS subfactors. Data-model fit for the predictive model was acceptable. Belief in the paranormal explained low variance over time in Perceived Stress and Somatic Complaints (between 2.4% and 4.2%). Findings supported the stability and reliability of the RPBS. In addition, they aligned with the notion that paranormal belief in the absence of high scores on cognitive-perceptual factors (e.g., transliminality and schizotypy), has a benign influence on perceived health.